Hermite–Hadamard- and Pachpatte-type integral inequalities for generalized subadditive functions in the fractal sense - Tingsong Du; Lei Xu (Miskolc Mathematical Notes)
In this paper, we establish the generalized Hermite–Hadamard- and Pachpatte-type integral inequalities for local fractional integrals via the generalized subadditive functions. In particular, we put forward a refined version of the generalized Hermite–Hadamard-type inequalities in the framework of fractal space.